Case Report: Disseminated Paracoccidioidomycosis and Strongyloides Hyperinfection in a Patient with Human T-Lymphotropic Virus Type 1/2 Infection - Montenegro-Idrogo, J (2024)
Co-occurrence of paracoccidioidomycosis and strongyloidiasis in immunosuppressed patients, particularly those infected with human T-lymphotropic virus type 1/2, is infrequent. We describe the case of a Peruvian farmer from the central jungle with human T-lymphotropic virus type 1/2 infection, with 2 months of illness characterized by respiratory and gastrointestinal symptoms associated with fever, weight loss, and enlarged lymph nodes. Strongyloides stercoralis and Paracoccidioides brasiliensis were isolated in sputum and bronchoalveolar lavage samples, respectively. The clinical evolution was favorable after the patient received ivermectin and amphotericin B. We hypothesize that autoinfestation by S. stercoralis in human T-lymphotropic virus type 1/2-infected patients may contribute to the disseminated presentation of Paracoccidioides spp. Understanding epidemiological context is crucial for suspecting opportunistic regional infections, particularly those that may coexist in immunosuppressed patients.